"A fin de que la ilusión sea completa": fotógrafos y fotografías en la ciudad de San José al finalizar el siglo XIX una contribución documental - Brenes Tencio, Guillermo (2013)
The main objective of this paper is to facilitate national and international researches to consult forty ads. Those are used to explore different uses of the photography in the City of San José, Costa Rica, in the last twenty years of the 19 th century. The ads are coming from the main printed mass media from 1881 and 1899.